Intersubject integration of humanities and management cycle disciplines - A. P. Avdeeva; Yu. A. Safonova (Вестник университета, 2022)
The problem of interdisciplinary educational integration reflects the realities of the modern world. Rapidly changing technologies set new requirements for the training of specialists capable of innovation. The study of the vertical and horizontal interdisciplinary integration resources for the disciplines of the humanities and management cycle is the purpose of this work. The structure of the article includes a theoretical and methodological analysis and an empirical part, represented by two stages of research (for socio-humanitarian and management disciplines). The article presents the results of modern views on the problem of interdisciplinary integration in higher education. The results of the theoretical analysis showed a mismatch between the depth of the theoretical study of the problem and the success of their practical implementation in the conditions of modern higher professional education. The complexity of the implementation is due to the changed psychological and socio-psychological characteristics of Generation Z students. Based on the theoretical analysis, a typology of interdisciplinary competencies was proposed. The aim of the empirical part of the study was to study the resources of vertical and horizontal integration at a technical university. Based on the empirical research, the possibilities of vertical and horizontal integration of the disciplines of the socio-humanitarian and management cycle were identified. An integrative matrix is presented. A promising direction for this topic is the development of an integrative module “Management workshop”.